Extraction of plant growth regulators present in Kappaphycus alvarezii sap using imidazolium based ionic liquids: detection and quantification by using HPLC-DAD technique. Issue 21 (29th September 2015) - Das, Arun Kumar; Prasad, Kamalesh
Abstract : Among three different hydrophobic ionic liquids, [Bmim][PF6 ] was found to extract selectively trans -zeatin and indole-3-acetic acid from Kappaphycus alvarezii sap. Abstract : Three different imidazolium based ionic liquids namely 1-butyl-3-methylimidazolium hexafluorophosphate [Bmim][PF6 ], 1-methyl-3-octylimidazolium tetrafluoroborate [Omim][BF4 ] and 1-butyl-3-methylimidazolium bis (trifluoromethylsulfonyl) imide [Bmim][NTf2 ] were used to extract plant growth regulators (PGRs) present in the sap ( K -sap) obtained by the mechanical expulsion from the fresh Kappaphycus alvarezii seaweed. [Bmim][PF6 ] was able to extract up to 65% of the total trans -zeatin and about 18% of the total indole-3-acetic acid (IAA) present in the sap as estimated by using a HPLC-DAD (diode array detector). However [Bmim][NTf2 ] was not able to extract any of the PGRs. Furthermore, addition of [Omim][BF4 ] to the sap resulted in the formation of an instant white precipitate with trans -zeatin preferentially bound on it. From the overall studies, it was concluded that [Bmim][PF6 ] can be effectively used to extract PGRs from seaweeds or plant extracts.